2006
DOI: 10.1177/000313480607200402
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Management of Patients with Traumatic Inferior Vena Cava Injuries

Abstract: The aim of this study was to determine factors that predict mortality in patients with traumatic inferior vena cava (IVC) injuries and to review the current management of this lethal injury. A 7-year retrospective review of all trauma patients with IVC injuries was performed. Factors associated with mortality were assessed by univariate analysis. Significant variables were included in a multivariate regression analysis model to determine independent predictors of mortality. Statistical significance was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 23 publications
3
73
0
9
Order By: Relevance
“…Of 15 papers reporting neurological outcomes, 84.6% (143 of the 169, range 50–100%) of patients returned to baseline . The survival outcome of EDT in US experience versus non‐US experiences was 6.3% (164 of the 2612, range 0–14.9) versus 11.9% (89 of the 745, range 0–33.3) respectively. Papers reporting outcomes of EDT performed in the pre‐hospital setting had survival rate of 16.3% (19 of the 116, range 10.25–33.33%) while those performed in the military had survival rate of 11.9% (13 of the 109, range 11.9–12.5%) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 15 papers reporting neurological outcomes, 84.6% (143 of the 169, range 50–100%) of patients returned to baseline . The survival outcome of EDT in US experience versus non‐US experiences was 6.3% (164 of the 2612, range 0–14.9) versus 11.9% (89 of the 745, range 0–33.3) respectively. Papers reporting outcomes of EDT performed in the pre‐hospital setting had survival rate of 16.3% (19 of the 116, range 10.25–33.33%) while those performed in the military had survival rate of 11.9% (13 of the 109, range 11.9–12.5%) …”
Section: Resultsmentioning
confidence: 99%
“…We identified 37 papers with a total of 3466 patients (Table ) . The overall incidence of patients undergoing EDT for penetrating trauma was 85.2% (1720 of the 2018, range 40–100%) .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in mortality rates in patients with abdominal IVC injuries has only been marginal over the past many decades. While 30% to 50% of cases with IVC injury exsanguinate to death before reaching the hospital, another 50% die despite the maximal possible hospital care [3]. Multiple factors predict the outcome of the patient in IVC injuries, including the mechanism of trauma, systolic blood pressure on presentation, response to resuscitation, part of IVC injured, and concomitant solid organ and vascular injuries [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cases have been reported where exploration of retroperitoneum started torrential bleed by removal of the tamponade effect of hematomas and death of a patient on table [2]. A study done by Huerta and Nguyen showed that 40% of the patients died of uncontrollable bleeding after the tamponade effect was released [3]. Hence, exploration or no exploration remains debatable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation